Climate change: carbon losses in the Alps - Kirk, Guy J. D. (Nature Publishing Group, 2016)
The response of the terrestrial carbon cycle to global change is one of the main uncertainties in current climate change predictions1. Most terrestrial carbon is held in soils as organic matter derived from the decay of plant material (Fig. 1). Soil organic matter accounts for roughly three times more carbon than living vegetation, and for more carbon than vegetation and the atmosphere combined. Because elevated atmospheric CO2 concentrations have a fertilizing effect on plant growth, anthropogenic CO2 emissions have triggered increases in the land carbon sink2. However, models predict that other factors — such as water and nutrients — will eventually become limiting to plant growth, and hence to the land carbon sink. In contrast, the turnover of soil organic matter producing CO2 is expected to increase as the Earth warms. As a result, simulations using coupled carbon–climate models predict that the land surface will become a net source of CO2 before the end of the century, leading to a feedback loop between climate and soil carbon losses: increased emissions of CO2 from soil organic matter will lead to enhanced warming, which may then feedback to cause further soil organic matter losses. Prietzel and colleagues3, writing in Nature Geoscience, now provide evidence that warming has already caused a decline in soil organic matter in the German Alps.
Keywords: Biogeochemistry; Carbon cycle; Climate-change impacts; Forest ecology